2014
DOI: 10.1111/hae.12392
|View full text |Cite
|
Sign up to set email alerts
|

Total ankle replacement in patients with haemophilia and virus infections – a safe alternative to ankle arthrodesis?

Abstract: Despite reliable results of ankle fusion for advanced haemophilic arthropathy, total ankle replacement (TAR) may be functionally advantageous. There is only very limited literature data available on TAR in patients with haemophilia. The objective of this study is to evaluate the short- and mid-term results after TAR in patients with end-stage haemophilic ankle arthropathy and concomitant virus infections. In a retrospective study, results after eleven TAR in 10 patients with severe (n = 8) and moderate (n = 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 36 publications
2
36
0
7
Order By: Relevance
“…A recent article has identified five studies , which analysed the short and mid‐term follow‐up of TAR in haemophilic patients. These studies totalled 33 TARs in 28 haemophilia patients and showed good rates of pain relief and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…A recent article has identified five studies , which analysed the short and mid‐term follow‐up of TAR in haemophilic patients. These studies totalled 33 TARs in 28 haemophilia patients and showed good rates of pain relief and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…In patients without prosthesis failure, there were no radiographic signs for prosthesis loosening or subsidence. The adjacent joint status remained comparable to the preoperative status [80]. Recently, Kotela et al [72] published a case series of three patients with bleeding disorders treated by TAR using a three-component prosthesis.…”
Section: Total Ankle Replacementmentioning
confidence: 63%
“…All available clinical studies reporting TAR outcomes in patients with bleeding disorders have demonstrated significant pain relief [65][66][67][68][69][70][71][72][76][77][78]80,81]. Most studies reported improved functionality, including increased ankle range of motion, postoperatively [65][66][67][68]72,75,76,79,80,82]. However, the observed increase in range of motion was overall very low with an average of <10° (Table 3).…”
Section: Total Ankle Replacementmentioning
confidence: 99%
“…This is remarkable despite the high rate of PWH with a severe form of the disease (45.7%) and concomitant viral infections (50%). In elective joint replacement surgery, the complication rate has been reported to be significantly higher than in the normal population [18]. However, the two observed refractures after minor traumas of the distal radius might be due to the higher prevalence of osteoporosis in PWH [19,20].…”
Section: Discussionmentioning
confidence: 99%